SILICOSIS, A WORK-RELATED DISEASE IN CONSTRUCTION WORKERS AND MINERS EXPOSED TO SILICA DUST - Mustofa, Syazili (Jurnal Kedokteran Universitas Lampung, 2025)
Silicosis is a fibrotic lung disease caused by the inhalation, retention, and reaction to crystalline silica. The primary factors contributing to the pathogenesis of silicosis are dust particles and the body's response, particularly the respiratory tract's reaction to these dust particles. Silica is a naturally occurring substance found in some types of rocks, sand, and clay. Silicosis primarily affects workers exposed to silica dust in occupations such as construction and mining. The mediators that play the most significant role in the pathogenesis of silicosis are Tumor Necrosis Factor (TNF)-α, Interleukin (IL)-6, IL-8, the activity of platelet-derived growth factor (PDGF), and transforming growth factor (TGF)-β. The major criteria for diagnosing silicosis include a significant history of silica dust exposure, characteristic radiological abnormalities (such as pulmonary nodules on chest X-rays or CT scans), and sometimes clinical symptoms, including a progressive cough and shortness of breath. The management of silicosis is symptomatic, meaning it is only aimed at reducing symptoms. It is very important to eliminate the source of exposure to prevent the disease from worsening. Keywords: silicosis, pathogenesis, diagnosis, treatment